Spending Natural Resource Revenues in an Altruistic Growth Model - Elisabeth Hermann Frederiksen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2006)
This paper examines how revenues from a natural resource interact with growth and welfare in an overlapping generations model with altruism. The revenues are allocated between public productive services and direct transfers to members of society by spending policies. We analyze how these policies influence the dynamics, and how the dynamics are influenced by the abundance of the revenue. Abundant revenues may harm growth, but growth and welfare can be oppositely affected. We also provide the socially optimal policy. Overall, the analysis suggests that variation in the strength of altruism and in spending policies may be part of the reason why natural resources seem to affect economic performance across nations differently.
Keywords: D64; O41; Q33; Q38; 330; natural resources; economic growth; welfare; altruism; Natürliche Ressourcen; Wirtschaftswachstum; Sozialstaat; Altruismus; Overlapping Generations; Theorie